The Effectiveness of Project-Based Learning Through Tiktok in Improving Student's Understanding of Procedure Texts - Mira Dinda Fatimatu Syarifah Mira; Heris Hendriana; Enung Nurhayati (JLER (Journal of Language Education Research), 2024)
This study examines the effectiveness of project-based learning through TikTok in improving student’s understanding of Indonesian procedural text. TikTok as a popular social media platform was chosen due to its potential to attract student’s interest and engagement in the learning process. The research method used is qualitative research with data collection techniques through observation, interviews, and questionnaires involving 30 students. The results showed that project-based learning through TikTok was well implemented, encouraging student’s active participation and collaboration. Most students gave positive perceptions towards the use of TikTok, feeling that this media made learning more interesting, helped them understand the material better, and improved creativity and collaborative skills. In addition, the use of TikTok proved effective in improving student’s understanding of procedure texts, with the majority of students reporting improvements in conceptual understanding, memory, and retention of the material. Overall, this study confirms that the integration of TikTok in learning provides a significant positive impact, making learning more interactive and relevant to student’s needs in the digital age. This conclusion demonstrates the importance of exploring and utilizing social media as a tool in education to improve learning quality and student engagement.